Acipenser ruthenus Linnaeus 1758 ... - Litz, Thomas O.; The, Stefan Koerber Introduction (Zenodo, 2014)
A. ruthenus Linnaeus, 1758 T first record Mentioned for Uruguay in T (p. 19) remarks introduced exotic species! origin Arctic rivers; Europe and Middle East: Black Sea, Sea of Azov, White Sea and Caspian Sea watersheds ... : Published as part of Litz, Thomas O. & The, Stefan Koerber Introduction, 2014, Check List of the Freshwater Fishes of Uruguay (CLOFF-UY)., pp. 1-40 in Ichthyological Contributions of PecesCriollos 28 on page 5, DOI: 10.5281/zenodo.11558256 ...